Fall from height: a case report - Zasa, Michele (Acta Biomedica Atenei Parmensis, 2015)
The manuscript reports the case of a 16-year-old boy who fell from a height of 15 meters while having a cellphone conversation. Surprisingly, only minor injuries were reported. Prognostic factors related to falls from height are still debated; the present case is a further contribution to the discussion.